The Effect of Drainage System and Natural System on Flood in Kuala Lumpur, Malaysia - Azizan, Muhammad Azizi; Muhammad Ammar Shafi,; Mohd Zarir Yusoff, (Research in Management of Technology and Business, 2023)
Malaysia has been hit by frequent floods, with disastrous consequences. Monsoonal floods have caused significant damage during the last few decades. Many factors are driving the occurrence of flash flood to happen. Some of the factors of flooding are drainage systems and natural system. Flooding has many negative effects on the economy, environment and social. The quantitative approach was used in this study. Using online Google Forms, 384 questionnaires were distributed to the people in Kuala Lumpur. The results of this study were analysed descriptively and correlated using Statistical Package for Social Science (SPSS) version 20.0. The study results show that all objectives and hypotheses have been achieved and accepted. There is a positive correlation between the independent variable and dependent variable, with a significant positive relationship between the factor of flood and the effect of flood. The limitations of this study included a limited number of respondents, samples and selection issues and its only focus on Kuala Lumpur. This study provided some recommendations for future research.